Pernikahan Beda Agama Pernikahan Beda Agama pada Surat Al-Baqarah Ayat 221: Analisis Hermeneutika Friedrich Schleiermacher - Ubaidillah, Rofiatul Ubaidillah; Kurniati, Nabilah (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
Interpretation of QS. Al-Baqarah verse 221 regarding interfaith marriages always experiences shifts in meaning.  This research aims to find out the literal message about interfaith marriage in the QS. Al-Baqarah verse 221. This research method uses a type of literature by collecting primary and secondary literature, then the researcher analyzes it using a romantic analysis approach which has two stages, namely grammatical analysis of the text and analysis of the author's psychological condition. The results of this research show that the law on marriage between people of different religions is permitted with two notes, namely: first, marriage between different religions is permitted only for non-Muslims who believe in one god (Arianism), what is meant is Arianism Christians, considering that at that time Christians were divided. into two groups, namely Arianism and Anathasianism. Second, it is permissible to marry ahlul kitab in question who is a Christian who is able to maintain his honor, not a polytheist. The implications of this research are in completing the understanding of texts that are often overlooked. Especially Schleiermacher's hermeneutical analysis.